Genome-Wide Analysis of MYB Gene Family in Chinese Bayberry (Morella rubra) and Identification of Members Regulating Flavonoid Biosynthesis - Cao, Yunlin; Jia, Huimin; Xing, Mengyun; Jin, Rong; Grierson, Donald; Gao, Zhongshan; Sun, Chongde; Chen, Kunsong; Xu, Changjie; Li, Xian (Frontiers in Plant Science, 2021)
Chinese bayberry (Morella rubra), the most economically important fruit tree in the Myricaceae family, is a rich source of natural flavonoids. Recently the Chinese bayberry genome has been sequenced, and this provides an opportunity to investigate the organization and evolutionary characteristics of MrMYB genes from a whole genome view. In the present study, we performed the genome-wide analysis of MYB genes in Chinese bayberry and identified 174 MrMYB transcription factors (TFs), including 122 R2R3-MYBs, 43 1R-MYBs, two 3R-MYBs, one 4R-MYB, and six atypical MYBs. Collinearity analysis indicated that both syntenic and tandem duplications contributed to expansion of the MrMYB gene family. Analysis of transcript levels revealed the distinct expression patterns of different MrMYB genes, and those which may play important roles in leaf and flower development. Through phylogenetic analysis and correlation analyses, nine MrMYB TFs were selected as candidates regulating flavonoid biosynthesis. By using dual-luciferase assays, MrMYB12 was shown to trans-activate the MrFLS1 promoter, and MrMYB39 and MrMYB58a trans-activated the MrLAR1 promoter. In addition, overexpression of 35S::MrMYB12 caused a significant increase in flavonol contents and induced the expression of NtCHS, NtF3H and NtFLS in transgenic tobacco leaves and flowers and significantly reduced anthocyanin accumulation, resulting in pale-pink or pure white flowers. This indicates that MrMYB12 redirected the flux away from anthocyanin biosynthesis resulting in higher flavonol content. The present study provides valuable information for understanding the classification, gene and motif structure, evolution and predicted functions of the MrMYB gene family and identifies MYBs regulating different aspects of flavonoid biosynthesis in Chinese bayberry.